BOCES Field Trip Guide - Nassau County Board of Cooperative Educational Services, Westbury, NY.; Nassau County Board of Cooperative Educational Services, Westbury, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
An effective and comprehensive guide to possible field trips for Nassau County (New York) elementary and secondary students covers places of interest in Nassau and Suffolk counties and in New York City. Recognizing that field trips can have great importance in the learning process, especially if they are directly related to the curriculum, the compilers have drawn the guide up along major curriculum lines--language and communication arts, science, social studies, fine arts. It includes many career exploration trips, sections on environmental and outdoor education and health. The guide is divided into elementary and secondary sections; major curriculum areas are subdivided first by locality and then by minor curriculum areas. Each entry gives descriptive information, recommendations for grade level, advance preparation, group size, fees involved, time required, visiting times, and information regarding parking and other facilities. Photographs sketches, cross referencing, and an index facilitate use. The introduction and the teaching approaches given at the beginning of each section give information regarding planning, correlation with curriculum, use of additional media and materials in conjunction with the trips, and suggest some specific points to cover. School districts preparing a similar publication can refer to this outline. (JMB)
Educational level discussed: Elementary Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Resources; Educational Resources; Elementary Education; Field Instruction; Field Trips; Guides; Resource Materials; School Community Relationship; Secondary Education; Teaching Guides; New York